Research on the Computer Case Design of 3D Human Animation Visual Experience. (3rd November 2021) - Liu, Kai; Yang, Qinghan; Lu, Yuhao; Zhang, Taoyu; Chen, Shuo
Abstract : In the animation industry, with the development of computer software and hardware technology, a new technology began to emerge, that is, three-dimensional animation. Three-dimensional animation software first creates a virtual world in the computer. In this virtual three-dimensional world, the designer builds the model and scene according to the shape and size of the object to be represented and then sets the motion trajectory of the model, the motion of the virtual camera, and the scene according to the requirements. When setting other animation parameters, we need to assign specific materials to the model and turn on lights. When all this is completed, the computer can automatically calculate and generate the final picture. The software Maya can just help animators to complete this work. When using Maya, we can apply many professional courses such as action design, scene design, and storyboarding script design that we have learned. Maya is a 3D software with convenient operability. It can combine the rendered sequence frames with AE to show unique animations. Therefore, the three-dimensional production method is preferred in the production method. The production of animation based on the 3D software Maya brings infinite challenges. At the same time, it also helps everyone grow and has a good position for our employment direction.